The ambience composing adequate housing for low income elderly - Luzia Cristina Antoniossi Monteiro; Vania Aparecida Gurian Varoto; Nayara Mendes Silva; Aldora Eugênia Freire (Serviço Social em Revista, 2018)
Brazil faces challenges with the increasing proportion of elderly in the total population of the country. Although the Federal Constitution establishes housing as a fundamental right, low-income seniors have difficulty to achieve it. Living in dignity pervades objective conditions and reaches subjective aspects, preponderant in the preservation of identity and of belonging the place, that is the meaning of ambience. This article analyzes the ambience in the formation of adequate housing in an exclusive condominium for low-income seniors. With longevity rises the demand for housing, because it increases the number of elderly living on their own - challenge for public policies that need to rethink places that promote participation in the community and quality of life.